Control of the Cretaceous Paleofluid Potential on the Source-Distal Lithologic Reservoirs in the Western Tabei Area of the Tarim Basin. (11th April 2022) - Chen, Jun; Dong, Ruixia; Kou, Longjiang; Yang, Xianzhang; Chen, Bintao; Meng, Xiangxia; Dai, Dongdong
Abstract : The Cretaceous clastic oil and gas reservoirs in the western Tabei area of the Tarim Basin are far away from source rocks (source-distal), and the hydrocarbons mainly originate from Triassic continental source rocks in the northern Kuqa Depression. Early exploration focused on structural oil and gas reservoirs, and yet, with deepening of exploration practice, exploration has shifted from structural oil and gas reservoirs to lithologic reservoirs. In such context, under guidance of the theory of migration and accumulation for source-distal reservoirs, the key accumulation period of Triassic source rocks is determined, and the migration path of oil and gas is clarified. According to the geological characteristics of the study area, the impression method and sequence ratio method are used to restore the paleoburial depth, and the Fillippone formula is used to restore the paleopressure. Based on Hubbert's theory, the paleofluid potential field of Triassic oil and gas in the Neogene Kangcun period is reasonably reconstructed. These combined with the planar structural evolution of Cretaceous reveal the preferential source-distal migration paths and directions of oil and gas. The favorable area of oil and gas accumulation is demarcated, and then, the facies belts with favorable lithology have been identified. The research results show the following: (1) The hydrocarbons of the Cretaceous oil and gas reservoirs originate from the Triassic source rocks. The Neogene Kangcun period is the key accumulation period. Hydrocarbons migrate to the western Tabei area along the Cretaceous basal unconformities and Late Yanshanian faults. (2) The paleofluid potential field of the Cretaceous during the key accumulation period shows the characteristics of "being high in the north and low in the south, " which is consistent with the gradual decrease of fluid potential along the migration distance from the northern hydrocarbon generation center (Kuqa Depression) to the south slope, and coincides with the main distribution range of source rocks in the Kuqa Depression. On the basis of the aforementioned, four preferential source-distal migration paths and directions of hydrocarbons have been clarified, and the Yudong-Yingmaili area is confirmed as a favorable area for the source-distal migration and accumulation of hydrocarbons into the Cretaceous. (3) In terms of the favorable areas for source-distal oil and gas migration and accumulation to Cretaceous strata, the forward distal end and lateral flanks of the branched retrogradational delta are the favorable facies belts for the next exploration of lithologic oil and gas resources. The recent breakthroughs in the lithologic reservoirs of wells D7 and M46 have confirmed that the findings of this research on the preferential source-distal migration paths and accumulation positions of hydrocarbons are of great guiding values for exploration deployment of Cretaceous lithologic reservoirs far away from source rocks.